The effect of aqueous crude extract of ginger on the histology of corpus luteum and the concentration of hormones estrogen and progesterone in pregnant mice (Baghdad Science Journal, 2015)
This study was designed to investigate the effect of aqueous extract of ginger Zingiber officinale Roscoe on the histology of corpus luteum and the concentration of the hormones progesterone and estrogen during the first trimester of pregnancy (0 - 7) days from fertilization. 30 pregnant mice were divided into five experimental groups: control group (administrated with distilled water), and four groups treated at doses (284, 568, 1136,1420 mg / kg), orally administrated , daily with (0.1 ml). Microscopic examination results have shown histopathological changes in corpus luteum included: Pyknosis in some nuclei of granulosa cells, Karyorrhexis, Karyolysis in some granulosa cells, and necrosis in corpus luteum, with additional significant decrease in the average of diameters of corpus luteum at level (P